SQLMVED: SQL injection runtime prevention system based on multi-variant execution - Bolin MA; Zheng ZHANG; Hao LIU; Jiangxing WU (Tongxin xuebao)
The effectiveness of combining SQL statement parsing with randomization to defend against SQL injection attack (SQLIA) was based on the fact that attackers did not know about the current method of randomization adopted by system.Therefore, once attackers had mastered the current method of randomization who can launch effective SQLIA.In order to solve this problem, a SQL injection runtime prevention system based on multi-variant execution was designed, the multi-variant apply randomization methods from any other, so that illegal SQL statements could not be parsed successfully by all variants.Even if attackers had mastered the method of randomization, illegal SQL statements could only be parsed successfully by a certain variant at most, meanwhile the parsing results of multiple variants were voted to find the abnormality in time and block attack path.The prototype system SQLMVED is implemented for Web services and experiments show that the prototype can effectively defeat SQLIA.